2005
DOI: 10.1111/j.1471-4159.2004.02893.x
|View full text |Cite
|
Sign up to set email alerts
|

Low atmospheric oxygen avoids maturation, senescence and cell death of murine mesencephalic neural precursors

Abstract: The efficient generation of specific brain cells in vitro may serve as a source of cells for brain repair in several devastating neurological diseases. Production of dopaminergic neurons from precursor cells for transplantation in Parkinson's disease has become a major research goal. We found that murine mesencephalic neurospheres were viable and proliferated, preserved telomerase activity, pluripotency and dopaminergic commitment for many weeks when cultured in 3% O 2 , whereas exposing these cells to 21% oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
2
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(105 citation statements)
references
References 48 publications
5
97
2
1
Order By: Relevance
“…Our in vivo data support the conclusion that the low oxygen atmospheric culture (3%) represents rather the physiological environment of the nervous tissue (average 4.6% O 2 ) than the so called hypoxic condition, because the observation that hyperoxia stimulates dopaminergic neurogenesis fits to previous in vitro studies, showing that proliferation and dopaminergic differentiation capacity of isolated midbrain dopaminergic NPCs depend on optimized oxygen levels: oxygen conditions of 3%-5% enhance long-term expansion and reduce spontaneous differentiation and cell senescence of dopaminergic progenitors in vitro [18][19][20]48]. However, severe hypoxia (<1% O 2 ) as well as normoxia (21% O 2 ) represses their proliferation and promotes spontaneous differentiation [17,34].…”
Section: /Nurr1mentioning
confidence: 86%
See 1 more Smart Citation
“…Our in vivo data support the conclusion that the low oxygen atmospheric culture (3%) represents rather the physiological environment of the nervous tissue (average 4.6% O 2 ) than the so called hypoxic condition, because the observation that hyperoxia stimulates dopaminergic neurogenesis fits to previous in vitro studies, showing that proliferation and dopaminergic differentiation capacity of isolated midbrain dopaminergic NPCs depend on optimized oxygen levels: oxygen conditions of 3%-5% enhance long-term expansion and reduce spontaneous differentiation and cell senescence of dopaminergic progenitors in vitro [18][19][20]48]. However, severe hypoxia (<1% O 2 ) as well as normoxia (21% O 2 ) represses their proliferation and promotes spontaneous differentiation [17,34].…”
Section: /Nurr1mentioning
confidence: 86%
“…Low atmospheric oxygen levels of 3% confer long-term proliferation and stem cell maintenance of midbrain dopaminergic NPCs in vitro, including the conservation of their dopaminergic differentiation potential, and avoid senescence in various species, including mouse [18][19][20][21][22][23][24]. Further in vitro studies have shown that the oxygen-dependent transcription factor hypoxiainducible factor 1a (HIF-1a) is involved in these processes [15,25,26] and is responsible for the initial adaptive response of cells to oxygen variations [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, near-physiological oxygen tensions (5-6%) improve the efficiency of induced pluripotent stem cell generation (79). Several studies on in vitro differentiation of neural stem cells have shown that low oxygen levels promote proliferation, survival and multipotency as compared to normoxic oxygen levels (80)(81)(82)(83)(84)(85)(86). Hematopoietic stem cells (HSCs) in the bone marrow have been proposed to exist in a low oxygen milieu (87,88).…”
Section: Hypoxia and The Stem Cell Phenotypementioning
confidence: 99%
“…Tissue samples were incubated in 0.1 mg/ml papain (Roche, Mannheim, Germany)/DNase solution (100 g/ml; Roche) for 30 min at 37°C, rinsed in PBS, incubated in antipain (50 g/ml; Roche) for 30 min at 37°C, and finally homogenized by gentle triturating using a firepolished Pasteur pipette. The cells were expanded as a monolayer culture by plating onto polyornithine-fibronectin precoated dishes in a density of 20,000 cells/cm 2 (Milosevic et al, 2005). The cells were maintained in serum-free DMEM (high glucose)/F-12 mixture (1:1) medium and supplemented with 20 ng/ml human recombinant epidermal growth factor and 20 ng/ml basic fibroblast growth factor (both from PromoCell, Heidelberg, Germany).…”
Section: Conditional Inactivation Of Hif-1␣ In Npcsmentioning
confidence: 99%
“…It is necessary to understand the mechanisms governing cell proliferation, dopaminergic differentiation, and senescence of NPCs to facilitate clinical therapies (Sharpless and DePinho, 2004). Reduced oxygen tension is now recognized as a common requirement for successful expansion and dopaminergic differentiation of NPCs (Ivanovic et al, 2000;Morrison et al, 2000;Studer et al, 2000;Storch et al, 2001;Milosevic et al, 2005). Low, physiologic oxygen conditions help maintain the undifferentiated state in mouse NPCs, but the molecular mechanisms underlying oxygen effects on NPCs are essentially unknown (Milosevic et al, 2005).…”
Section: Introductionmentioning
confidence: 99%